Advances in Injectable Polysaccharide Hydrogels for Site-Specific Drug Delivery - Sharma, Vijay; Singh, Gurvinder Pal; Sharma, Gyanendra Kumar; Singh, Maneesh Kumar; Verma, Navneet; Sharma, Saurabh (Journal of Pharmacy Practice and Community Medicine, 2026)
Injectable polysaccharide hydrogels are emerging as promising platforms for sitespecific drug delivery because they can be administered minimally invasively, conform to complex tissue geometries, and form in situ depots for sustained local drug release. This review summarizes recent advances in injectable systems based on chitosan, alginate, hyaluronic acid, dextran, and cellulose derivatives, with emphasis on their sources, structural features, and suitability for injectable formulations. Key hydrogel formation strategies-including physical, chemical, enzymatic, and stimulitriggered crosslinking-are discussed alongside critical physicochemical and biological properties that govern injectability, mechanical performance, swelling, and biocompatibility. Drug loading approaches and diffusion-, degradation-, and stimuliresponsive release mechanisms are outlined, with applications highlighted in cancer therapy, tissue engineering, regenerative medicine, wound healing, and localized infection control. Emerging smart and hybrid nanocomposite hydrogels, together with current challenges in stability, scalability, reproducibility, and regulation, are considered to frame future directions for successful clinical translation of these versatile biomaterials.
Keywords: Biocompatibility; Injectable hydrogels; Polysaccharides; Site-specific drug delivery; Stimuli-responsive systems